Compressed sensing with signal averaging for improved sensitivity and motion artifact reduction in fluorine‐19 MRI. (1st October 2020) - Darçot, Emeline; Yerly, Jérôme; Hilbert, Tom; Colotti, Roberto; Najdenovska, Elena; Kober, Tobias; Stuber, Matthias; van Heeswijk, Ruud B.
Abstract : Fluorine‐19 ( 19 F) MRI of injected perfluorocarbon emulsions (PFCs) allows for the non‐invasive quantification of inflammation and cell tracking, but suffers from a low signal‐to‐noise ratio and extended scan time. To address this limitation, we tested the hypotheses that a 19 F MRI pulse sequence that combines a specific undersampling regime with signal averaging has both increased sensitivity and robustness against motion artifacts compared with a non‐averaged fully sampled pulse sequence, when both datasets are reconstructed with compressed sensing. As a proof of principle, numerical simulations and phantom experiments were performed on selected variable ranges to characterize the point spread function of undersampling patterns, as well as the vulnerability to noise of undersampling and reconstruction parameters with paired numbers of x signal averages and acceleration factor x (NA x ‐AF x ). The numerical simulations demonstrated that a probability density function that uses 25% of the samples to fully sample the k ‐space central area allowed for an optimal balance between limited blurring and artifact incoherence. At all investigated noise levels, the Dice similarity coefficient (DSC) strongly depended on the regularization parameters and acceleration factor. In phantoms, the motion robustness of an NA8‐AF8 undersampling pattern versus NA1‐AF1 was evaluated with simulated and real motion patterns. Differences were assessed with the DSC, which was consistently higher for the NA8‐AF8 compared with the NA1‐AF1 strategy, for both simulated and real cyclic motion patterns ( P < 0.001). Both strategies were validated in vivo in mice ( n = 2) injected with perfluoropolyether. Here, the images displayed a sharper delineation of the liver with the NA8‐AF8 strategy than with the NA1‐AF1 strategy. In conclusion, we validated the hypotheses that in 19 F MRI the combination of undersampling and averaging improves both the sensitivity and the robustness against motion artifacts. Abstract : A fluorine‐19 ( 19 F) MRI acquisition‐reconstruction strategy that combines eight‐fold k ‐space undersampling and compressed sensing with eight‐fold signal averaging (NA8‐AF8) was developed and compared with a fully sampled denoised reconstruction (NA1‐AF1). In simulated and real motion phantom experiments, NA8‐AF8 yielded a higher sensitivity per unit time as well as a greater robustness against motion artifacts than NA1‐AF1. in vivo in mice injected with perfluoropolyether, NA8‐AF8 resulted in a sharper organ delineation than the NA1‐AF1 strategy.